The leadership shadow how to recognize and avoid derailment, hubris and overdrive - Haan, Erik de; Kasozi, Anthony (Kogan Page, 2014)
"To ensure a competitive advantage, senior executives have to push themselves and their teams hard. Under stress and challenges, the qualities that executives have relied on to get them to the top can ultimately lead to organizational catastrophes. The Leadership Shadow tackles the dark side of leadership, delving into what causes leadership derailment and how to avoid it. It also explains the ways in which a leader's performance can affect not just themselves, but the organization as a whole. Using examples drawn from various executives' experiences and descriptions of psychological behaviors based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and the Hogan Personality Inventory model, the authors demonstrate how to find stability in the face of uncertainty, resilience in the face of grueling demand, and psychological equilibrium as a leader. "--